(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the connection between allegory and stylistic devices, highlighting the unique features that distinguish allegory from other literary styles. Allegory, as a narrative technique, relies heavily on the interplay of symbolic representations and stylistic elements to convey deeper meanings beyond the literal text. The study examines how metaphors, similes, personifications, and other rhetorical tools are employed in allegorical works to create multi-layered interpretations. Additionally, the paper delves into the differences between allegory and other literary styles such as symbolism, metaphorical writing, and direct narrative techniques. By comparing allegory’s reliance on extended symbolism to other approaches, the article emphasizes its role as a powerful medium for moral, philosophical, and political commentary. The findings contribute to a better understanding of allegory’s unique position in the literary landscape and its enduring relevance in modern literature